2018
DOI: 10.1098/rspb.2017.1957
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the complete larval settlement process confirms Crisp's model of surface selectivity by barnacles

Abstract: For barnacle cypris larvae at the point of settlement, selection of an appropriate surface is critical. Since post-settlement relocation is usually impossible, barnacles have evolved finely tuned surface-sensing capabilities to identify suitable substrata, and a temporary adhesion system for extensive surface exploration. The pattern of exploratory behaviour appears complex and may last for several hours, imposing significant barriers to quantitative measurement. Here, we employ a novel tracking system that en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 33 publications
(55 reference statements)
1
24
0
2
Order By: Relevance
“…The ten most abundant top ions were selected for MS/MS analysis with a normalized collision energy of 30. MS 2 data acquisition was performed at 17,500 MS resolution with an automatic gain control of 1e 5 and a maximum injection time of 100 ms. The isolation window was set to 1.3 m/z with an under fill ratio of 0.4%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ten most abundant top ions were selected for MS/MS analysis with a normalized collision energy of 30. MS 2 data acquisition was performed at 17,500 MS resolution with an automatic gain control of 1e 5 and a maximum injection time of 100 ms. The isolation window was set to 1.3 m/z with an under fill ratio of 0.4%.…”
Section: Methodsmentioning
confidence: 99%
“…Cyprids have numerous specialized adaptations for sensing and attaching to appropriate surfaces, such as compound eyes that appear only briefly in the cyprid before being lost during metamorphosis to the adult 1 . A pair of highly dextrous antennules enable bipedal walking during the pre-attachment exploratory phase [3][4][5] and 11 individually identifiable sensory setae 6 set cyprids apart from the settling larvae of other marine invertebrates. Uniquely among Crustacea, many barnacle species must position themselves close to a future mate at attachment but also allow for growth and adhesion in the adult form 7 , which has led to supreme surface selectivity.…”
mentioning
confidence: 99%
“…and physicochemical properties, e.g., surface textures (Berntsson et al, 2000;Aldred et al, 2010;Chaw et al, 2011), hydrophobicity (Chaw and Birch, 2009;Phang et al, 2009;Guo et al, 2014), surface energy, and charge (Petrone et al, 2011;Di Fino et al, 2014) were also found to influence cyprid surface exploration. Using more complex video-/tracking-based approaches, the dynamic cyprid surface exploration process under different conditions was also monitored, offering a real-time and quantitative method of understanding the settling behaviors of a cyprid by measuring its swimming velocity, step length and duration, body movements, footprint deposition, and so on (Marechal et al, 2004;Andersson et al, 2009;Chaw and Birch, 2009;Maleschlijski et al, 2012;Aldred et al, 2013bAldred et al, , 2018Maleshlijski et al, 2016).…”
Section: Surface Exploration: Cyprid Temporary Adhesionmentioning
confidence: 99%
“…During settlement, the barnacle cyprid larvae respond to chemical and physical cues in the surrounding environment while swimming in the water column as well as when exploring various surfaces. The surface exploration comprises wide search, close search, and inspection behaviours that precede the settling decision leading to permanent adhesion through the release of cement (Crisp 1976;Aldred et al 2018). Because adult barnacles are permanently attached, cyprid substratum selection is the main factor determining the local abundance and distribution of barnacles in natural populations as well as on marine constructions (eg ships' hulls), and is therefore a key question in barnacle biology and ecology (Thiyagarajan 2010).…”
Section: Introductionmentioning
confidence: 99%